Pengaruh Religiusitas, Budaya, Literasi Keuangan dan Lingkungan Sosial terhadap Perilaku Menabung Gen Z (Jurnal Simki Economic, 2025)
This study examines the influence of religiosity, culture, financial literacy, and social environment on the savings behavior of generation Z, with a case study of high school students in Ambulu District. This study is motivated by the high level of consumptiveness in generation Z, which affects savings habits. Data from the Katadata Insight Center (KIC) shows that most generation Z rarely save or separate savings from daily expenses. Based on the Theory of Planned Behavior, this quantitative study collected data through questionnaires distributed to 100 high school students. Data analysis was carried out using multiple linear regression to test the impact of independent variables on savings behavior. The findings show that the level of religiosity, culture, financial literacy, and social context have a significant influence on savings behavior. Religiosity forms financial discipline and responsibility; culture encourages thrift and planning; financial literacy helps decision making; and a supportive social environment encourages interest in saving. This model is able to explain 73.4% of the variation in savings behavior, while the remaining 26.6% is influenced by other factors outside the model, such as personal motivation, education, economic conditions, or other external influences.